An Analysis of Idiomatic Expressions in the Script of The Good Dinosaur Movie - Dewi, Salma Tsabita; Kustantinah, Indri; Karima, Festi Himatu (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
The aims of the study focused on analyzing the types and the meaning of idiomatic expressions in the script of The Good Dinosaur Movie proposed by the theory of McCarthy and O’Dell (2010). This study used a descriptive qualitative method. The data from this study were taken from the script of The Good Dinosaur movie produced by Pixar Animated studios and released by Walt Disney Picture. The data were analyzed by identifying the idiomatic expression in the movie script into 6 types and classifying the word in each type of idiomatic expression. The researcher classified words into idiomatic expression by reading all the script in detail and watching the movie. Then the researcher analyzing the word by trying to find the correct word or the real meaning, after that the researcher can decide the word was called as an idiomatic expression. In theory, McCarthy and O’Dell divide idiomatic expressions into six types namely fixed statement, proverb, simile, cliché and euphemism. The researcher found four types of idiomatic expressions in this movie, they are 18 (56%) data types of fixed statement, 11 (34%) data types of proverb, 2 (6%) data types of simile, 1 (4%) data types of cliché, and the most dominant type of idiomatic expressions is fixed statement. The researcher suggest to future researchers to analyze the idiomatic expressions in other literary work such as song lyrics, drama, novel, etc